Benefits of Side‐Firing Optical Fibers in Endoscopic Laser Treatment of the Larynx. (5th September 2022) - DeVore, Elliana Kirsh; Chiluisa, Alex J.; Minch, Emily V.; Mihaleva, Rositsa; Do, Hoang; Tougas, Ryan; Fichera, Loris; Carroll, Thomas L.
Abstract : Objective: To elucidate potential tissue coverage of side‐firing optical fibers in office‐based endoscopic laser treatment of larynx, as well as to demonstrate their enhanced ability to address challenging anatomic areas. Method: We performed a comparative study of four different fiber designs: a traditional forward‐facing fiber, and three side‐firing fibers that emit light at an angle of 45°, 70°, and 90°, respectively. The study was conducted in simulation, using eight three‐dimensional models of the human larynx generated from microtomography x‐ray scans. A computer program simulated the insertion of the endoscope into the larynx, and the Möller–Trumbore algorithm was used to simulate the application of laser light. Results: Side‐firing laser fibers increased potential tissue coverage by a mean of 50.2 (standard deviation [SD] 25.8), 73.8 (SD 41.3), and 84.0 (SD 47.6) percent for angles of 45°, 70°, and 90°, respectively, compared to forward‐facing fibers. Angled fibers provided access to areas of the larynx considered difficult to address by traditional methods, including the infraglottis, laryngeal ventricle, and right vocal fold. Conclusion: Simulation results suggest that side‐firing optical fibers have the potential to enhance anatomical access during in‐office endoscopic laser procedures in the larynx. Further research is needed to better understand the benefits and any potential risks or contraindications of side‐firing optical fibers. Level of Evidence: NA Laryngoscope, 133:1205–1210, 2023 Abstract :